On receiving a first copy of Notes and Records: George Sarton to A. V. Hill, 24 February 1942 - Fox, Robert (The Royal Society, 2013)
George Sarton, often regarded as the founder of the discipline of the history of science, appears to have first seen Notes and Records of the Royal Society in 1942. His letter of acknowledgement to A. V. Hill conveys both his pleasure at the publication (which the Royal Society had launched in 1938) and his frustration in trying to persuade scientists and ‘humanists’ of the value of his work. The letter also records Sarton's sadness at the death of his Harvard colleague L. J. Henderson, a fellow-worker in his campaign to ‘humanize science’.